“Age of Lovecraft”? Anthropocene Monsters in (New) Weird Narrative - Ulstein, Gry (Nordlit, 2019)
This paper considers whether the twenty-first-century resurgence of H. P. Lovecraft and weird fiction can be read as a conceptual parallel to the Anthropocene epoch, taking Carl H. Sederholm and Jeffrey Andrew Weinstock’s The Age of Lovecraft as a starting-point. The assumption is that the two ‘ages’ are historically and thematically linked through the ‘monsters’ that inhabit them; monsters that include—but are not limited to—extensions, reproductions, and evolutions of Lovecraft’s writings. Preoccupied with environmental issues such as global climate change, the twenty-first-century imaginary has conjured monsters that appear to have much in common with early twentieth-century cosmic horror stories. Considering the renewed interest in Lovecraft and the weird, such developments raise the question: What can (weird) monsters tell us about the Anthropocene moment? This paper maps the ‘monstrous’ in the discourses emerging from the Anthropocene epoch and ‘The Age of Lovecraft’ by considering (new) weird narratives from contemporary literature, graphic novels, film, TV, and video games. Mindful of on-going discussions within ecocriticism, philosophy, and critical theory, the paper discusses a handful of unconventional texts to investigate the potential of the weird for expressing Anthropocene anxieties and for approaching nonhuman realities from new angles.
Keywords: Anthropocene; ecology; cosmic horror; Lovecraft; new weird